Conjugated donor–acceptor copolymers derived from phenylenevinylene and trisubstituted pyridine units: synthesis, optical, and electrochemical properties. (September 2015) - Hariharan, A.; Subramanian, K.; Alagar, M.; Dinakaran, K.
Copolymers having intramolecular donor–acceptor systems encompassing trisubstituted pyridine derivatives as acceptor and phenylenevinylene (PPV) unit as a donor segment were synthesized. In addition, thiophene-containing random terpolymer PPVPYT via palladium-catalyzing Heck coupling reaction is reported. The novel-substituted pyridine monomers (PYBr) are synthesized by adopting a one-pot synthesis method using p -toluenesulfonic acid as catalyst in ethanol medium, which results in an excellent yield of about 95%. All the copolymers Poly phenylenevinylene-co-Pyridine derivatives (PPVPY) and terpolymers of Polyphenylenevinylene-co-Pyridine and Thiophene (PPVPYT) are found to be soluble in organic solvents, such as tetrahydrofuran, chloroform, and N, N -dimethylformamide. The molecular weights of the synthesized polymers were characterized by gel permeation chromatography (GPC), and their chemical structures were confirmed by infra red and nuclear magnetic resonance spectroscopies. The electrochemical band gaps of PPVPY-1, PPVPY-2, and PPVPY-3 copolymers are estimated to be 2.55, 2.48, and 2.0, respectively. Similarly, the band gap of PPVPY75T25, PPVPY50T50, and PPVPY25T75 random copolymers are estimated as 2.31, 1.95, and 2.23, respectively. These polymers also show excellent optical and thermal properties.